Leisure, sport and tourism, politics, policy and planning - Veal, Anthony James, 1945- (Oxford : CAB International, 2017)
A multi-disciplinary approach to policy making and planning in the leisure, sport and tourism sectors, this book provides an introduction for students. It examines theoretical issues underpinning public sector policy making, debates around the role of the state versus market, and models of organisational decision-making.
Elektronická reprodukce
Keywords: politika cestovního ruchu -- Velká Británie; cestovní ruch; volný čas; sport; tourism policy -- Great Britain; tourism; leisure; sport; učebnice vysokých škol; elektronické knihy; e-knihy online; textbooks (higher); electronic books; e-books online